2022
DOI: 10.1093/arclin/acac068
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Abnormally Low Neuropsychological Scores in Post-COVID-19 Syndrome: the Geneva COVID-COG Cohort

Abstract: Objective Several studies have reported poor long-term neuropsychological performances in patients following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, but none has yet considered the effect of administering multiple intercorrelated neuropsychological tests and assessed the frequency of cognitive deficits in a normative population. Our aim was therefore to assess the presence of cumulative neuropsychological deficits in an actual post-coronavirus disease of 2019 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…Therefore, we cannot exclude that the mild group also exhibits reduced neuropsychological scores in comparison to a control group as has been described in the literature. That said, a recent study by our group did not show a significant accumulation of deficits in the group of mild patients compared to a simulated normative population, while the moderate and severe groups presented a significantly greater accumulation of neuropsychological deficits (Voruz, Allali, et al, 2022 ; Voruz, Cionca, et al, 2022 ; Voruz, de Alcântara, et al, 2022 ). Moreover, our moderate and severe groups are potentially not representative of the population of hospitalized SARS‐CoV‐2 patients because of their lack of comorbidities.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Therefore, we cannot exclude that the mild group also exhibits reduced neuropsychological scores in comparison to a control group as has been described in the literature. That said, a recent study by our group did not show a significant accumulation of deficits in the group of mild patients compared to a simulated normative population, while the moderate and severe groups presented a significantly greater accumulation of neuropsychological deficits (Voruz, Allali, et al, 2022 ; Voruz, Cionca, et al, 2022 ; Voruz, de Alcântara, et al, 2022 ). Moreover, our moderate and severe groups are potentially not representative of the population of hospitalized SARS‐CoV‐2 patients because of their lack of comorbidities.…”
Section: Discussionmentioning
confidence: 46%
“…The experimental design and tests used are comparable to those used in a previous published study (Voruz, Allali, et al, 2022 ; Voruz, Cionca, et al, 2022 ; Voruz, de Alcântara, et al, 2022 ).…”
Section: Methodsmentioning
confidence: 91%
“…A total of 27 out of 32 articles reported negative effects of COVID-19 infection during the medium period (5–8 months). As in the short period, most of the authors found a significant general cognitive decline [ 60 , 61 , 62 , 63 , 64 , 68 , 69 , 70 , 73 , 77 , 78 , 82 , 83 , 84 , 85 ], in particular, in memory [ 62 , 65 , 66 , 74 , 77 , 81 , 85 , 86 , 87 , 88 ], verbal fluency [ 62 , 65 , 66 , 71 , 72 , 88 ], executive functions [ 65 , 69 , 72 , 74 , 75 , 81 , 87 , 88 ] and attention tasks [ 65 , 72 , 76 , 89 ]. Three studies did not report significant effects on cognitive performance in hospitalized people that resulted positive in the SARS CoV-2 nasopharyngeal test compared to those with no history of the virus [ 37 , 38 , 79 ]; while, in the Pilotto et al [ 83 ] and Stallmach et al [ 84 ] study, a very low percentage of people with COVID-19 infection showed the presence of cognitive decline.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, this status is often referred to as ‘Long COVID’ [ 116 , 117 ], or ‘brain fog’ with accompanied clinical symptoms, such as low energy, insomnia, problems in concentration and spatial orientation and difficulty in finding the right words [ 118 ]. In particular, some studies reported a decrease in short-and-long term memory performance [ 62 , 65 , 66 , 74 , 77 , 81 , 85 , 86 , 87 , 88 ], in verbal fluency [ 62 , 65 , 66 , 71 , 72 , 88 ], in executive functions [ 65 , 69 , 72 , 74 , 75 , 81 , 87 , 88 ] and in selective attention tasks [ 65 , 72 , 76 , 89 ]. It is likely the case, as suggested by previous studies, that these cognitive deficits occurred as a consequence of respiratory symptoms severity due to the pandemic [ 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, direct and indirect costs of the post-COVID-19 condition have been recently estimated to range from US$140 to US$600 billion annually [ 4 ]. Moreover, one of the most prevalent and disabling symptoms of the post-COVID-19 condition is “brain fog”, reflecting the persistence of neurocognitive symptoms such as confusion, forgetfulness, a lack of focus and mental clarity, and fatigue [ 1 , 5 ]. Those were recently categorised as neuropsychological post-COVID-19 conditions, with 30%-40% of patients suffering or complaining of such symptoms [ 5 ], requiring exhaustive neuropsychological assessments from neuropsychologists.…”
mentioning
confidence: 99%